Petrografi dan Geokimia Unsur Utama Granitoid Pulau Bangka: Kajian Awal Tektonomagmatisme - Widana, Kurnia Setiawan (BRIN Publishing, 2013)
Bangka Island is composed by Klabat Granite and its granitoid variations. This study aims to investigate the characteristics of granitoid Bangka Island to be applied in the study of magmatism, tectonic situations and relationships developed in granitoid for possible exploration. The methodology used by observations with a thin section of rock (petrography) and secondary major elements analysis from previous research. Granitoid samples are collected from Western, Southern, Central and East (Belinyu). Granitoid ages range from Late Permian to Late Triassic. Petrographic analysis showed dominant granitoid type as Alkali Feldspar–Syeno Granite, whereas geochemical analysis as Alkali -Syeno Granite. SiO2 variation diagram shows declining in the proportion of the major elements CaO, MgO, TiO2, Al2O3 and P2O5 with increasing SiO2 influenced by affinity fractionation as calc-alkalic magma with high K content. Affinity can be formed on continental arc where subduction and collision involved. Preliminary result granitoid typology as peraluminous, with I type. In Central and Eastern Bangka (Belinyu) characterized by high proportion of magnetite, magnesian, and more primitive, while S type in the South and West Bangka are characterized by high K2O and the presence of abundant biotite + muscovite + cordierite.